Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2015)
A dataset containing 10677136 species occurrences available in GBIF matching the query: { "TaxonKey" : [ "is Picidae" ] } The dataset includes 10677136 records from 922 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0004219-150922153815467/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences